2022
DOI: 10.4081/ejtm.2022.10504
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive-behavioral aspects of the Mulligan concept of manual therapy: A systematic review

Abstract: Low back pain (LBP) is a common clinical problem imposing a prominent socio-economic burden. The purpose of this systematic review was to investigate the biopsychosocial effects of the Mulligan Concept (MC) of manual therapy (MT) when applied to patient's with LBP. Three researchers independently evaluated the literature quality, and completed a review on five online databases (Medline, Cochrane Library, Science Direct, ProQuest and Google Scholar) for articles published from January 1st 2010 to November 20th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Tambekar et al, in their article, concluded that both the Mulligan and Butler approaches demonstrated that SLR and discomfort were reduced right after the intervention [ 14 ]. In their paper, Athanasiadis et al came to the conclusion that there is currently little and conflicting data supporting the biopsychosocial benefits of Mulligan procedures for treating patients with LBP [ 15 ]. More research on the bio-psychosocial components of the Mulligan will strengthen the body of data supporting the management of LBP patients with manual therapy and enhance clinical judgment when it comes to non-pharmacological treatment options [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tambekar et al, in their article, concluded that both the Mulligan and Butler approaches demonstrated that SLR and discomfort were reduced right after the intervention [ 14 ]. In their paper, Athanasiadis et al came to the conclusion that there is currently little and conflicting data supporting the biopsychosocial benefits of Mulligan procedures for treating patients with LBP [ 15 ]. More research on the bio-psychosocial components of the Mulligan will strengthen the body of data supporting the management of LBP patients with manual therapy and enhance clinical judgment when it comes to non-pharmacological treatment options [ 15 ].…”
Section: Discussionmentioning
confidence: 99%